Changing Oil Prices, Exchange Rates and its Impact on Inflation in Pakistan - Hammad Hussain (Journal of Accounting and Finance in Emerging Economies, 2022)
Purpose: The key objective of the analysis is to explore the impact of oil prices and exchange rates on the inflation rate in Pakistan by using annual time-series data from the period 1980 to 2020.